Geographical distribution of the potato crop in the district of Abo – Ghraib, 2005- 2011 (Journal of the College of Education for Women, 2019)
Source of energy and protein Field crops considered an important needed for humanbeings Due of this fact increases should appear in the quantities of their production in order tomeet the needs of continuous increasing in the population of the glope year after year ;otherwise, an increase in the gap between the amount of production and consumption willoccur .This study aims to reveal the geographical distribution of the potato crop in the districtof Abu – Ghraib. For this purpose, a study conducted about the cultivated areas, productionand crop yields per Dunam for period of 7 years lasted from 2005-2011.The study shows that potato is one of the most important field crops that are grown inthe Abu – Ghraib district. Nevertheeless, the highest rates of cultivated areas and quantities ofproduction of this crop are appeared in counties of AL-Nesir Oa Al-Salam: As the County of17/ Radwania come in the first rank among all the administrative units in the district of Abo –Ghraib regarding the amount of productivity.